Sporothrix brasiliensis: A growing hazard in the Northern area of Buenos Aires Province? - Etchecopaz, Alejandro Nazareno (2020)
We wish to provide some perspective to all microbiologists, veterinarians and medical doctors with regard to four human and three feline cases of sporotrichosis that occurred during November 2018 and May 2019 in three rural areas of the northern part of the province of Buenos Aires, Argentina. Since 2006, few cases of feline sporothrichosis occurred sporadically in the same geographical areas of our country1,5. However, it is stricking that in a term of six months seven cases have occurred, two of them as small outbreaks with zoonotic transmission to human. The first small outbreak occurred in Los Polvorines, and included a veterinarian (female, 30 years old) who was scratched by a sick cat (a 2-year-old female mongrel neutered free-roaming domestic cat) and the infant owner of it (female, 3 years old) who had been in contact with it. The veterinarian developed the lymphocutaneous form of the disease whereas the young girl the fixed form. The second outbreak, occurred in Tigre, and affected the veterinarian (female, 37 years old) and the owner of the cat (female, 35 years old) who were scratched by the sick cat (a 2-year-old male mongrel intact free-roaming domestic cat). The last case only involved a 4-year-old male mongrel neutered free-roaming cat from Partido 3 de Febrero, that presented multifocal cutaneous crusted and ulcerated lesions. In all cases, diagnosis was performed at Cátedra de Enfermedades Infecciosas, Facultad de Ciencias Veterinarias, Universidad de Buenos Aires. In brief, samples of cutaneous exudates were collected through sterile swabs from the ulcerative lesions of all human patients and cats. Nail tip fragments from both thoracic members were also obtained from one cat. Direct examination of tissue samples from the four patients and feline lesions revealed the presence of Sporothrix yeast-like organisms. Fungal cultures and molecular identification of the strains were performed3. In all cases, fungal isolates were identified as Sporothrix brasiliensis, the most virulent species in the genus Sporothrix. Oral itraconazole or saturated solution of potassium iodide for at least three months were the treatment of choice for these cases.We would like to shed some more light on the implications associated with this emerging hazard. In Brazil, a neighboring country of Argentina, the number of reported cases of zoonotic infections from feline-related sporotrichosis due to S. brasiliensis has reached alarming proportions4,6,7.Bearing in mind the epidemic magnitude of this mycosis in Brazil, is mandatory to control this fungal disease through basic educational, sanitarian and political measures. Since Argentina is an immense country, and many geographical areas have favorable conditions for Sportothrix growth, the prevalence of cases must be much higher than is estimated according to the literature. However, the fact that sporotrichosis is not a reportable disease makes very difficult to determine the real scale of zoonotic sporotrichosis. Consciousness of zoonotic and epizootic potential transmission of sporotrichosis should be promoted among veterinarians and animal-related-workers. Therefore, epidemiological research works from different parts of Argentina are really essential for gaining insight into the prevalence of this emerging fungi. Once available, such information will be extremely valuable both for designing new assays for its rapid detection as well as for the implementation of proper therapy. Bearing in mind the concept of ?one health?, the experience described in the present letter highlights the need for future strategies for sporotrichosis surveillance, control and prevention.Finally, at the moment of writing this manuscript, it was reported an outbreak of sporotrichosis with probable zoonotic transmission to humans in El Calafate, Province of Santa Cruz, Argentina2. Up to our knowledge, this outbreak represents the southernmost outbreak location of sporotrichosis.